Vitamin D intoxication-induced hypercalcemia in a geriatric patient: a case report: Hipercalcemia inducida por intoxicación con vitamina D en una paciente geriátrica: reporte de un caso - Dextre-Vilchez, Sergio Armando (2024)
Introduction: Hypercalcemia secondary to vitamin D intoxication is a rare condition resulting from inadequate prescription. It is characterized by nonspecific symptomatology and can produce severe neurological, muscular, gastrointestinal, renal, and cardiovascular manifestations. Clinical case: We describe the case of an 86-year-old woman with a history of vitamin D supplementation for three months after hip arthroplasty. The initial presentation was gastrointestinal symptoms and sensorimotor disturbance. Hypercalcemia was found upon evaluation. After ruling out the main organic causes, vitamin D intoxication was suspected, which was confirmed after testing for 25-hydroxyvitamin D levels. Correction of hypercalcemia was performed, and the patient had a favorable clinical evolution.  Conclusion: It is important to consider vitamin D intoxication as a differential diagnosis of hypercalcemia in geriatric patients and to ensure adequate monitoring of the prescription of vitamin supplements.